2019
DOI: 10.1002/suco.201900039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sulfates effects in perlite‐based geopolymer

Abstract: Condition deterioration of the concrete, especially in corrosive environments, is one of the most common imperfection and disadvantages of reinforced concrete structures. Sulfates' main damages are expansion and loss of strength. Geopolymers are one of the newest structural materials that have been widely developed in recent years for use in sustainable designs. Geopolymers are environmentally friendly and considered as green materials since they are effective in sustainable and eco‐friendly material design co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It generally contains more than 70% silica and can be used in plaster, concrete, mortar, and ceiling flooring [23,24]. When heated up to 800-1150 • C, its volume increases by 10-30% and turns into low-density, high-heat-resistant, and white-colored expanded perlite (EP) [25,26]. EP is used as a heat and sound insulation material in the construction industry [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It generally contains more than 70% silica and can be used in plaster, concrete, mortar, and ceiling flooring [23,24]. When heated up to 800-1150 • C, its volume increases by 10-30% and turns into low-density, high-heat-resistant, and white-colored expanded perlite (EP) [25,26]. EP is used as a heat and sound insulation material in the construction industry [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that ground calcined perlite (GCP) can be used in the production of geopolymers [26,27]. Increasing perlite fineness improves the compressive strength of geopolymer and chemical resistance to aggressive environments [1,25]. In general, fine perlite reduces pores in geopolymer, creates a more compact structure, and provides more strength [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Test results indicate that the usage of waste marble improves concrete permeation properties . The mechanical properties of concrete improve by the use of perlite‐based geopolymer, or binary and ternary mixes of fly ash and silica fume, or scoria aggregates . The usage of metakaolin and diatomite in concrete with water reducing agent, to adjust workability instead of water, promotes an improvement in both the microstructure and the hardened state features such as porosity and mechanical strength .…”
Section: Introductionmentioning
confidence: 99%